IDENTIFICATION OF LEAD AND CADMIUM LEVELS IN WHITE CABBAGE (Brassica rapa L.), SOIL, AND IRRIGATION WATER OF URBAN AGRICULTURAL SITES IN THE PHILIPPINES - Hardiyanto Hardiyanto; Constancio C. De Guzman (Indonesian Agency for Agricultural Research and Development, 2008)
Urban agriculture comprises a variety of farming systems, ranging from subsistence to fully commercialized agriculture. Pollution from automobile exhaust, industrial and commercialactivities may affect humans, crops, soil, and water in and around urban agriculture areas. The research aimed to investigate the level and distribution of lead (Pb) and cadmium (Cd) in white cabbage (Brassica rapa L.), soil, and irrigation water taken from urban sites. The research was conducted in Las Piñas and Parañaque, Metro Manila, Philippines. The field area was divided into three sections based on its distance from the main road (0, 25, and 50 m). Irrigation water was taken from canal (Las Piñas) and river (Parañaque). Pb and Cd contents of the extract were measured by Atomic Absorption Spectrophotometry. Combined analysis over locations was used. The relationship between distance from the main road and metal contents was measured by Pearson’s correlation. Based on combined analyses, highly significant difference over locations was only showed on Cd content in white cabbage. Cd content in white cabbage grown in Parañaque was higher than that cultivated in Las Piñas, while Cd content in the soil between both sites was comparable.The average Pb content (1.09 µg g-1 dry weight) was highest in the white cabbage grown right beside the main road. A similar trend was also observed in the soil, with the highest concentration being recorded at 26 µg g-1 dry weight. There was a negative relationship between distance from the main road and Pb and Cd contents in white cabbage and the soil. Level of Pb in water taken from the canal and river was similar (0.12 mg l-1), whereaslevels of Cd were 0.0084 and 0.0095 mg l-1, respectively. In general, the concentrations of Pb and Cd in white cabbage and soil as well as irrigation water were still in the acceptable limits. In terms of environmental hazards and polluted city environment, it seems that big cities in Indonesia especially Jakarta and Surabaya have the same problem with the Philippines. Therefore, it is suggested that the study on heavy metal contaminationin several crops, especially those grown along the main road, should be conducted.